Morse Theoretic Methods in Nonlinear Analysis and in Symplectic Topology - Biran, Paul; Cornea, Octav; Lalonde, François (NATO Science Series II: Mathematics, Physics and Chemistry, Mathematics, Physics and Chemistry, 2006)
The papers collected in this volume are contributions to the 43rd session of the Seminaire ´ de mathematiques ´ superieures ´ (SMS) on "Morse Theoretic Methods in Nonlinear Analysis and Symplectic Topology." This session took place at the Universite ´ de Montreal ´ in July 2004 and was a NATO Advanced Study Institute (ASI). The aim of the ASI was to bring together young researchers from various parts of the world and to present to them some of the most signi cant recent advances in these areas. More than 77 mathematicians from 17 countries followed the 12 series of lectures and participated in the lively exchange of ideas. The lectures covered an ample spectrum of subjects which are re ected in the present volume: Morse theory and related techniques in in nite dim- sional spaces, Floer theory and its recent extensions and generalizations, Morse and Floer theory in relation to string topology, generating functions, structure of the group of Hamiltonian di?eomorphisms and related dynamical problems, applications to robotics and many others. We thank all our main speakers for their stimulating lectures and all p- ticipants for creating a friendly atmosphere during the meeting. We also thank Ms. Diane Belanger ´ , our administrative assistant, for her help with the organi- tion and Mr. Andre ´ Montpetit, our technical editor, for his help in the preparation of the volume.